Overt and Null Subject Variation in Ammani Arabic: Distribution, Constraints, and Implications - Рахаф Хатер; Марван Джаррах; Мохаммад Аль-Бадаві; Екаб Аль-Шавашрех (Психолінгвістика, 2024)
Purpose. This article investigates the distribution of overt and null subject pronouns in Ammani Arabic (AA) from a variationist perspective, identifying social and linguistic constraints that shape pronoun expression. The study examines how age, gender, and educational attainment, alongside grammatical person, sentence polarity (positive vs. negative), tense, clause type (root vs. embedded), and verbal component (verbal vs. verbless), impact the choice between overt and null pronouns.